2017
DOI: 10.1039/c7ta02552a
|View full text |Cite
|
Sign up to set email alerts
|

Poly(p-phenylene terephthamide) embedded in a polysulfone as the substrate for improving compaction resistance and adhesion of a thin film composite polyamide membrane

Abstract: The compaction resistance of a substrate and the adhesion of a polyamide skin layer onto the substrate were improved by the incorporation of PPTA into the substrate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(23 citation statements)
references
References 53 publications
0
21
0
2
Order By: Relevance
“…Obviously, these SiO 2 /PVDF substrates were apt to have rougher surfaces than the neat PVDF substrate, due to the few nanoparticles segregation on surface . Besides, a rougher surface meant a larger surface area (see SAD in Table ), resulting in a higher adhesive force between the rejection and support layer . However, when the content is high enough, the agglomeration of nanoparticles appears inevitably as seen in Figure and would significantly weaken the dispersion of the nanoparticles in membrane surface, resulting in the decrease of membrane roughness.…”
Section: Resultsmentioning
confidence: 99%
“…Obviously, these SiO 2 /PVDF substrates were apt to have rougher surfaces than the neat PVDF substrate, due to the few nanoparticles segregation on surface . Besides, a rougher surface meant a larger surface area (see SAD in Table ), resulting in a higher adhesive force between the rejection and support layer . However, when the content is high enough, the agglomeration of nanoparticles appears inevitably as seen in Figure and would significantly weaken the dispersion of the nanoparticles in membrane surface, resulting in the decrease of membrane roughness.…”
Section: Resultsmentioning
confidence: 99%
“…However, the hydraulic pressures under which the TFC membranes and corresponding supports were tested typically differ by at least an order of magnitude and the conditioning times are often less than an hour [37,42,43]. Under high-pressure RO, substantial mechanical deformation is expected, which would lead to higher resistance than the value observed under lower pressure [44,45]. For example, Shi et al [44] reported an 8% decrease in the DI water flux of a porous support as transmembrane pressure increases from 1.4 MPa to 1.6 MPa.…”
Section: Discussionmentioning
confidence: 99%
“…Under high-pressure RO, substantial mechanical deformation is expected, which would lead to higher resistance than the value observed under lower pressure [44,45]. For example, Shi et al [44] reported an 8% decrease in the DI water flux of a porous support as transmembrane pressure increases from 1.4 MPa to 1.6 MPa. Considering both the high pressure required for seawater desalination by an RO membrane (up to 8 MPa [1]) and the extended period of expected operation, the resistance of the porous support might be substantially higher than the value estimated using a typical UF operating pressure.…”
Section: Discussionmentioning
confidence: 99%
“…PSF is a classical membrane material for the preparation of ultraltration, [21][22][23][24] nanoltration, 25,26 and matrix membranes [27][28][29] due to its outstanding properties of thermal stability, chemical resistance, high mechanical strength, and wide aperture adjustment range. 30 Hydrophobic SiO 2 nanoparticles have the features of small particle size, narrow particle size distribution, and large surface area, 31 which play an important role in making a rough and superhydrophobic surface.…”
Section: Introductionmentioning
confidence: 99%